Challenging poverty through Proverbs : an African transformational hermeneutic - Masenya, Madipoane (Old Testament essays, 2006)
In his ground-breaking doctoral thesis, 'An African Perspective on Poverty Proverbs in the Book of Proverbs: An Analysis for Transformational Possibilities', Lechion Peter Kimilike advocates what could be called 'a methodology from the African grassroots' or 'a methodology from below'. Poverty is a challenge facing many people at grassroots level on the African continent. These African masses readily find themselves at home as they interact with the Old Testament text on account of the many similarities that exist between the Old Testament and African world views. Challenging the elitist Western approaches to the Book of Proverbs, particularly how the scholars in question have failed to use the book to resuscitate the voice of the poor from the proverbs on poverty in this book, Kimilike proposes what can be called an African transformational approach to the Old Testament. He uses the latter, not only to suggest a possible popular social location for poverty proverbs in Proverbs, but also, drawing largely on the rich African lore that is African proverbs, to reread Old Testament poverty proverbs to challenge poverty in Africa. This paper is an attempt to make a brief presentation of Kimilike's African holistic approach to the interpretation of the Book of Proverbs, an approach mainly shaped by the researcher's African context.